Groin pain in athletes - Weber, Marc-André; Rehnitz, Christoph; Ott, Henning; Streich, Nikolaus (RöFo, 2013)
Groin pain in athletes is one of the most difficult to treat clinical entities in sports medicine. The reasons are the amount of differential diagnoses, complexity of pathophysiologic causes and the long time of limited participation in sport. In order to maximize efficient treatment, thorough diagnostics and a clear therapeutic regimen are crucial. To succeed with this issue, a close cooperation between physicians and radiologists is mandatory. MRI is gold standard in the diagnostic work-up of the principal differential diagnoses, such as muscle tears, avulsion injuries, stress fractures, tears of acetabular labrum, and osteitis pubis. The article gives a comprehensive overview of the special anatomy and biomechanics of the pubic region and of typical MRI findings in athletes with groin pain. The use of dedicated imaging protocols is also discussed.
Gesehen am 04.10.2021